The representation of Alistair Maclean's life as reflected in south by Java Head: a biographical study - Amalia, Hafida (COMMICAST, 2020)
This undergraduate thesis research aims to understand and inform the period of World War II experienced by the author Alistair MacLean from a military perspective rather than from a war leader. Because of this, the authors consider this research interesting because it can find the similarity and differences between the novel and Alistair MacLean.The writer applies the biographical approach as the basic of the analysis. The method of this analysis systematically used qualitative methods in compiling this research as the techniques library data sources, journal article, internet and all books dealing with this research, and the main textual data in South by Java Head. The results of this analysis indicate that in the military life of the war during World War II that seemed disciplined that they made a lifelong commitment to, it turns out there are still those who consciously committed acts of violation; similarity: Japanese Cruelty, Deadly Weapons ect, differences: The Deal Punishment. But there are also some positive knowledge, especially for readers.